Application of non-thermal floating electrode-dielectric barrier discharge plasma for Salmonella Enteritidis reduction and quality assessment in chicken breasts and skin - Eun Bi Jeon; Eun Ha Choi; Jun Sup Lim; Shin Young Park (Poultry Science, 2025)
Salmonella Enteritidis—primarily associated with chicken—is a global cause of foodborne enteritis in humans. However, no studies have confirmed or evaluated the effectiveness of floating electrode-dielectric barrier discharge (FE-DBD) plasma treatment on S. Enteritidis in raw chicken breasts or chicken skin. The antibacterial effects of FE-DBD plasma (2.8 kV, 47, N2 1.5 m/s, 1–60 min) against S. Enteritidis in raw chicken breasts and skin were evaluated in this study. When FE-DBD plasma treatment was applied for 10, 20, 30, 40, 50, and 60 min, S. Enteritidis decreased by 0.45−2.98 and 0.17−1.46 log CFU/g in chicken breasts and skin, respectively. The decimal reduction time (D-values) for chicken breasts and skin were calculated using first-order kinetics, yielding values of 21.32 and 40.32 min, respectively, with chicken skin showing higher resistance to FE-DBD plasma treatment. A quality analysis of pH, total volatile basic nitrogen (TVBN), and thiobarbituric acid reactive substances (TBARS) revealed that the pH of chicken breasts and skin significantly increased with treatment time, with the final pH reaching 6.03 and 5.95 in chicken breasts and skin after 60 min, respectively. Despite the observed increase in TVBN (chicken breasts: 5.15−5.31 mg/100 g; chicken skin: 7.16−7.30 mg/100 g) and TBARS (chicken breasts: 0.11−0.171 mg MDA/100 g; chicken skin: 0.13−0.19 mg MDA/100 g) values, they remained within acceptable limits. These results demonstrate that FE-DBD plasma is a promising non-thermal technology capable of reducing S. Enteritidis contamination in raw chicken while maintaining product quality, particularly in complex food matrices such as skin where treatment efficacy has been limited in prior studies.